PENERAPAN MEDIA AUDIO VISUAL UNTUK MENINGKATAN HASIL BELAJAR SERVIS PENDEK BULUTANGKIS PEGANGAN BACKHAND - Rahmat Hidayat; Sunardi Sunardi (PHEDHERAL, 2018)
This study aims to improve the short service learning outcomes badminton grip backhand  by using the application of audio visual media.               This research is a Classroom Action Research (PTK). The study was conducted in two cycles, with each cycle consisting of planning, action execution, observation, and reflection. The subjects of the study were students which amounted to 34 students consisting of 11 boys and 23 girls. Sources of data is by observation assessment of learning outcomes short serve badminton grip backhand. Data analysis using descriptive technique based on qualitative analysis with percentage.               The result of the allasis obtained from Chapter IV shows a gradual increase from the pre-cycle of cycle I and from cycle I of cycle II. This can be seen from the result of short service learning handles backhand show from 34 students there are 11 students or 32.35% complete and Not complete as many as 23 students or equal to 67.65%. Then the short service learning results of backhand handles shown in cycle I showed an increase of sebasar 38.24%, 24 students or 70.59% included in the category Completed and the remaining 10 Learners or 29.41% fall into the Unfinished category. In the second cycle improvement of learning outcomes of students better is equal to 20.59% of the cycle I or 58.83% of prasiklus. A total of 31 learners or equal to 91.18% enter the Taskas category and 3 students or equal to 8.82% into the Unfinished category               The conclusion of this research is the application of audio visual media can improve the learning result short service badminton handle backhand .